Limites da supremacia do interesse público quando contrapostos ao interesse do cidadão - Silva, Denise Martins Moura (2013)
This dissertation examines the stated principle of the supremacy of the public interest over private interest, which is considered in the Brazilian administrative law as one of its pillars, as opposed to the interests of the citizen. The objective is to examine whether this implicit principle really exists in the legal system. Therefore, based on introductory talks-about historical notes about administrative law and state power, and seek the origin and relevance of the principle of the supremacy of the public interest, investigating the indeterminate concept of the public interest as well as the various understandings light on this principle and its influence on the construction of administrative law with current reflections on essentially the period of the welfare state, in pursuit of achievement of full citizenship rights. Then goes on to investigate the situation of the individual, on the rights and guarantees inherent to human dignity. We continue doing an investigation on existing concepts about legal standard, detailing the concept of legal principle and identify proportionality as a measure for weighting of core values and not as a principle. The conclusion reached by pervades counterbalancing and the mitigation principle in favor of the democratic rule of law and protecting citizens.